The Influence of Toxic Parenting on Sibling Rivalry Among High School Students - Fitri, Riska Annisa; Erwinda, Lira (Journal of Counseling and Educational Research, 2024)
The purpose of this study is to find out whether there is an influence between toxic parenting and sibling rivalry and aims to see the picture of toxic parenting with sibling rivalry. The method used in this study uses a quantitative approach. The population and sample in this study are 113 students of SMK Ankes Tunas Harapan. Data were collected through two questionnaires, including the toxic parenting instrument and the sibling rivalry instrument. The data was analyzed using SPSS version 20 software with random sampling techniques. The analysis techniques used in testing variables are normality tests, linearity tests, and hypothesis tests using simple linear regression. The findings in this study are that there is a significant influence between toxic parenting (X) with sibling rivalry (Y).